PEMANFAATAN DAN KONSERVASI SUMBER DAYA AIR TANAH UNTUK KEBUTUHAN LAHAN PERTANIAN SAWAH DI DESA NANGA LABANG KECAMATAN BORONG KABUPATEN MANGGARAI TIMUR - Sinong, Felisianus Jodian; Wulakada, Hamza Huri; Pamungkas, Bella Theo Tomi (Jurnal Geografi, 2021)
The aimed of this research to find out 1) the availability of ground water in Nanga Labang Village 2) the volume of ground water used by farmers for irrigation of paddy fields during one planting period 3) what were the efforts made by the people of Nanga Labang Village in maintaining and protecting natural resources. water. The method used descriptive method with a quantitative approach, this type of research was survey research. Data collection techniques used interviews, observation, and documentation. Analysis of the data used formula for calculating water availability statically, calculating water needs which were presented in tabular form, as well as the results of field identification related to groundwater resource conservation efforts carried out by the people of Nanga Labang Village. The results of this study found the availability of ground water in the study area 83,731,200 m3/year. This availability was influenced by geological conditions, land cover, geomorphology, rainfall in the research area. The water demand in the research area was influenced by the area of land, the number of use of boreholes, the length of time pumping is carried out and the capital costs owned by the farmers. Planting Time. The conservation efforts that have been carried out have not been very visible to the community, so far the efforts that are often needed by the community are by making efficient use of water.